2010
DOI: 10.5539/jas.v2n3p49
|View full text |Cite
|
Sign up to set email alerts
|

Study of Genetic and Phenotypic Variability among Somaclones Induced by BAP and TDZ in Micropropagated Shoot Tips of Banana (Musa spp.) Using RAPD Markers

Abstract: The effects of different concentrations of Benzylaminopurine (BAP) and Thidiazuron (TDZ) on somaclonal variation based on genetic and phenotypic variability among micropropagated shoot tips of banana cultivars; 'Berangan Intan', 'Berangan' and 'Rastali' were studied. With the highest concentrations of both BAP and TDZ up to 44.4µM and 7.5 µM, respectively, most shoots were curled and other morphological changes such as hyperhydricity and undifferentiated shoots were observed. Detectable genetic changes to reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Several strategies such as morpho-physiological, biochemical, cytological, and DNA-based molecular markers approaches have been employed to maintain the genetic constancy of the in vitro regenerated plantlets. Detection of the genetic homogeneity in micropropagated plants using molecular techniques could be achieved with polymerase chain reaction (PCR)-based techniques such as random amplified polymorphic DNA (RAPD) and inter simple sequence repeat (ISSR) [ 43 , 44 ]. For plant crops that are difficult to breed or have a poor genetic basis, somaclonal variation can be a very useful option for breeders as a new option [ 45 ].…”
Section: Somatic Embryogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies such as morpho-physiological, biochemical, cytological, and DNA-based molecular markers approaches have been employed to maintain the genetic constancy of the in vitro regenerated plantlets. Detection of the genetic homogeneity in micropropagated plants using molecular techniques could be achieved with polymerase chain reaction (PCR)-based techniques such as random amplified polymorphic DNA (RAPD) and inter simple sequence repeat (ISSR) [ 43 , 44 ]. For plant crops that are difficult to breed or have a poor genetic basis, somaclonal variation can be a very useful option for breeders as a new option [ 45 ].…”
Section: Somatic Embryogenesismentioning
confidence: 99%
“…If the abnormality is the result of DNA modifications, it will be very difficult to reverse. Meanwhile, abnormalities caused by epigenetic modification may be reversible and the resulting abnormal embryos can regenerate to a perfect plantlet [ 43 , 134 , 199 , 200 ].…”
Section: Physiological Responses Of Plant Regenerationmentioning
confidence: 99%
“…Lopez et al, (2010) used TDZ to induce cacao somatic embryos while in this study used kinetin. According to Bidabadi et al (2010) and Jose et al, (2012), the types and concentrations of PGRs may have caused different level of somaclonal variations. The regenerated cacao plantlets carrying high frequency of allele losses and multiple mutations found in this study support previous finding reported by Lopez et al (2010).…”
Section: Somaclonal Variation Assessmentmentioning
confidence: 99%
“…Furthermore, it was also intricate to find out if the plantlets came from the same batch of multiplication; since number of subcultures was also a source of somaclonal variation [30]. Somaclonal variation is a common phenomenon that occurs in the banana tissue culture especially one with the polyploidy cultivar, such as Barangan (AAA) [31]. The somaclonal variation induced in in vitro culture influenced mitotic instability especially in regenerate abnormal metaphase [32].…”
Section: Effects Of Elf-emf On the Growth And Biochemical Characterismentioning
confidence: 99%